Reproduktion auf Eis gelegt?: Ethische Aspekte von Social Egg Freezing - Hofer-Ranz, Gabriel (Bioethik in Wissenschaft und Gesellschaft, 2022)
Cryopreservation of unfertilised oocytes constitutes a relatively new technology for the preservation of female fertility. This procedure is being increasingly utilised without any existing medical indications (‘social egg freezing’). Based on an empirical and legal analysis, this book tries to provide a moral evaluation of this controversial technique by discussing and assessing both its potential and risks, while focusing in detail on the relation between social egg freezing and the philosophical question of a good life. The author argues that a potential danger of this procedure lies in postponing existential life choices and thereby failing to achieve the goal of a broadly successful life.